Helminth fauna of Astyanax fasciatus Cuvier, 1819, in two distinct sites of the Taquari River, São Paulo State, Brazil - Acosta, Aline Angelina [UNESP]; Queiroz, Jamile Queiroz de [UNESP]; Brandão, H. [UNESP]; Silva, Reinaldo José da [UNESP] (Instituto Internacional de Ecologia, 2015)
This study assessed the helminth fauna of Astyanax fasciatus in two distinct sites of the Taquari River, São Paulo State, with 30 individuals sampled in a lotic site and 30 in a lentic site, recording the monogeneans: Cacatuocotyle paranaensis, Characithecium costaricensis, Diaphorocleidus kabatai, Jainus sp., Notozothecium sp. and Gyrodactylus sp., the digenean Antorchis lintoni and no-identified metacercariae; the nematode Procamallanus (Spirocamallanus) inopinatus and no-identified larvae. The mean abundances of total monogeneans (U = 1053; p = 0.042) and C. costaricensis (U = 1107; p = 0.005) were higher in the lotic site. This difference may be due to the higher density of the host population in the lotic site, and the water transparence in lentic environments that prevents A. fasciatus to form shoals, precluding the exchange of parasites with direct cycle within a host population. This study is the first report of the helminth fauna of A. fasciatus in the Taquari River, with ten taxa recorded, and reports A. fasciatus as a new host for Notozothecium sp. and C. paranaensis.

Este estudo avaliou a helmintofauna de Astyanax fasciatus em dois trechos distintos no rio Taquari, São Paulo, com 30 indivíduos coletados no trecho lótico e 30 no trecho lêntico, registrando os monogenóides: Cacatuocotyle paranaensis, Characithecium costaricensis, Diaphorocleidus kabatai, Jainus sp., Notozothecium sp. e Gyrodactylus sp., o digenético Antorchis lintoni e metacercárias não identificadas, o nematoide Procamallanus (Spirocamallanus) inopinatus e larvas não identificadas. A abundância média de monogenóides total (U = 1053; p = 0,042) e C. costaricensis (U = 1107; p = 0,005) foi maior no trecho lótico. Esta diferença pode ser devido à densidade mais alta da população de hospedeiros no trecho lótico e à transparência da água em trechos lênticos que previne a formação de cardumes de A. fasciatus e a troca de parasitas com ciclo direto dentro da população de hospedeiros. Este estudo é o primeiro registro da helmintofauna de A. fasciatus no rio Taquari, com dez taxa encontrados, e registra A. fasciatus como novo hospedeiro para os monogenóides Notozothecium sp. e C. paranaensis.
Fauna de helmintos de Astyanax fasciatus Cuvier, 1819, em dois locais distintos do rio Taquari, estado de São Paulo, Brasil
Keywords: Neotropical fish; Astyanax fasciatus; Parasites; Reservoir; Peixes Neotropicais; Astyanax fasciatus; Parasitas; Reservatório